Pemberdayaan Masyarakat Pada Pembuatan Blender Sampah Untuk Bahan Baku Biogas Di Perumahan Pondok Lakah Permai - yani prabowo; Suwasti Broto; Nazori AZ; Sujono Sujono; Akhmad Musafa; Peby Wahyu Purnawan; T.W. Wisjnuadji; Siswanto Siswanto (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2020)
Budi Luhur University in collaboration with residents of Pondok Lakah Permai Ciledug housing, collaborates in the field of household scale waste management to be used as biogas raw material. The problem faced by environmental managers is that waste is not transported then rot. To solve this problem, the waste is processed into biogas through a fermentation process. The fermentation process is used to break down organic waste into methane gas which can be used for cooking. The role of the community is needed to collect waste raw materials and sort organic and non-organic waste. The purpose of this community service activity is to empower residents to separate waste from household waste to be processed into biogas. The method used is to provide counseling and continue with the manufacture of a waste chopping blender to process the waste. The results of this service can be concluded that the first one has produced a biogas reactor unit and a waste crusher / blender, then after training to the target community on how to make a biogas reactor, the second conclusion is that the two communities can operate the tools that have been made and can also sort waste. as a raw material for biogas. In this activity, the community understands how to protect the environment and can operate a waste chopping biodigester and blender so that the waste that had been piling up is now processed into biogas.